BclI polymorphism of the glucocorticoid receptor and adrenal crisis in primary adrenal insufficiency - Zopf, Kathrin (Endocr Connect, 2017)
CONTEXT: Patients with primary adrenal insufficiency (PAI) or congenital adrenal hyperplasia (CAH) are at a high risk of adrenal crisis (AC). Glucocorticoid sensitivity is at least partially genetically determined by polymorphisms of the glucocorticoid receptor (GR). OBJECTIVES: To determine if a number of intercurrent illnesses and AC are associated with the GR gene polymorphism BclI in patients with PAI and CAH. DESIGN AND PATIENTS: This prospective, longitudinal study over 37.7 ± 10.1 months included 47 PAI and 25 CAH patients. During the study period, intercurrent illness episodes and AC were documented. RESULTS: The study period covered 223 patient years in which 21 AC occurred (9.4 AC/100 pat years). There were no significant differences between BclI polymorphisms (CC (n = 29), CG (n = 34) and GG (n = 9)) regarding BMI, hydrocortisone equivalent daily dose and blood pressure. We did not find a difference in the number of intercurrent illnesses/patient year among BclI polymorphisms (CC (1.5 ± 1.4/pat year), CG (1.2 ± 1.2/pat year) and GG (1.6 ± 2.2/pat year)). The occurrence of AC was not significantly different among the homozygous (GG) genotype (32.5 AC/100 pat years), the CC genotype (6.7 AC/100 pat years) and the CG genotype (4.9 AC/100 pat years). Concomitant hypothyroidism was the highest in the GG genotype group (5/9), compared to others (CC (11/29) and CG (11/34)). CONCLUSIONS: Although sample sizes were relatively small and results should be interpreted with caution, this study suggests that the GR gene polymorphism BclI may not be associated with the frequencies of intercurrent illnesses and AC.